Analisis Risiko Usaha Aksesoris Trezzya Berdasarkan Kerangka ISO 31000:2018 - Sarah Mutia Azahra; Almaira Sarah Junjunan; Nisa Febrianti; Muhammad Shoffan Anbiya; Alfiana Alfiana (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
MSMEs play a vital role in supporting Indonesia's economic growth, yet they frequently face challenges in maintaining business sustainability. One such challenge is the lack of effective risk management implementation. This study aims to analyze the implementation of risk management at the Trezzya Accessories MSME, a business engaged in the production and sale of handmade accessories and gifts. The analytical method used refers to the ISO 31000:2018 framework, which encompasses the identification, analysis, and assessment of risks, supported by a SWOT analysis to assess the business's strengths, weaknesses, opportunities, and threats. The results indicate that the main risks faced include operational, financial, and market risks, which significantly impact business sustainability. The implementation of mitigation strategies such as strengthening digital marketing, improving human resource skills, and more structured financial management is considered capable of minimizing potential losses and increasing business competitiveness. Thus, the implementation of ISO 31000-based risk management plays a crucial role in supporting the stability and sustainability of the Trezzya Accessories MSME amidst dynamic market competition.